Political Connections, Institutional Ownership and Earnings Quality in Manufacturing Companies in Indonesia - Dwi Anggraini, Septia; Subroto, Bambang; Andayani, Wuryan (The International Journal of Accounting and Business Society, 2023)
Purpose — This study aims to investigate the influence of political connections on earnings quality. In addition, this study also aims to investigate the influence of institutional ownership on the relationship between political connections and earnings quality. Design/methodology/approaches — This study uses a quantitative approach . The sample of this study are companies listed on the Indonesia Stock Exchange during the 2018-2020 period. The dependent variable in this study is earnings quality, the independent variable is political connections, and the moderating variable is institutional ownership. Hypothesis testing uses multiple regression analysis with the SPSS 18 test tool. Findings — The results of the study show that political connections have a negative effect on earnings quality. In addition, the results of this study also show that institutional ownership has a negative effect on the relationship between political connections and earnings quality. Practical implications — The results of the study have implications for companies and related authorities to consider the minimum or maximum number of politically connected company boards in serving in the company. In addition, the research results also provide implications for companies and related authorities to consider the minimum or maximum amount of institutional investor ownership in the company. Originality/value — This research is different from previous studies, because this research considers the existence of institutional ownership in the relationship between political connections and earnings quality. Paper type — Quantitative Research